Practicum & Internship Coordinators’ Experiences amid COVID-19 Emergency Remote Teaching - Alexander T Becnel; Sarah Irvin; Theodore Remley (Teaching and Supervision in Counseling, 2023)
Although recent literature addresses online pedagogy and online counselor education, few articles address the challenges faced by counselor educators during emergency remote teaching, an unplanned and unanticipated switch from in-person education to online education. To address this gap, we conducted a phenomenological study of the lived experiences of practicum and internship coordinators (N = 8) during the emergency remote teaching phase of the COVID-19 pandemic. Five themes emerged: (a) uncertainty, (b) adaptation to leadership, (c) changes to student experience, (d) personal support, and (e) readiness. Implications for counselor educators and supervisors are addressed.
Keywords: Practicum & amp; internship; COVID-19; clinical field experience; leadership